Inorganic porous drug delivery carriers - Rosenholm, Jessica (Henry Stewart Talks, 2020)
Drug delivery systems, Advantages and characteristics of porous materials, Mesoporous silica nanoparticles (MSNs), Material design aspects for drug delivery efficacy, Formulation aspects to be considered, Examples of in vitro cellular targeting, In vivo therapeutic delivery and detection